2003
DOI: 10.1191/1352458503ms893oa
|View full text |Cite
|
Sign up to set email alerts
|

The utility of computerized neuropsychological assessment of cognitive dysfunction in patients with relapsing-remitting multiple sclerosis

Abstract: Traditional paper-and-pencil neuropsychological batteries used to document cognitive deficits in multiple sclerosis (MS) patients lack timing precision. This makes it difficult to accurately measure psychomotor slowing, a central cognitive symptom of MS. Additionally, traditional batteries lack multiple alternate forms necessary to control for practice effects when assessing cognition over time. Finally such batteries are lengthy and expensive. Computerized neuropsychological batteries address many of these sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 31 publications
1
48
1
Order By: Relevance
“…Each of the nine subtests was assigned a value of zero if normal or 0.11 if abnormal. 15 Therefore, a patient with a score of zero showed ing, which may not be performed until the deficits are advanced. Even in so-called benign MS, difficulty in the ability to process information may be great enough to prevent employment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the nine subtests was assigned a value of zero if normal or 0.11 if abnormal. 15 Therefore, a patient with a score of zero showed ing, which may not be performed until the deficits are advanced. Even in so-called benign MS, difficulty in the ability to process information may be great enough to prevent employment.…”
Section: Methodsmentioning
confidence: 99%
“…Weekly intramuscular (IM) interferon beta-1a (IFNb1a) has shown statistically significant neuropsychological benefit compared with placebo in a 2-year multicenter treatment trial using a comprehensive neuropsychological battery 14 and a computerized battery. 15 A 2-year trial with glatiramer acetate (GA) did not show any benefit over placebo with a comprehensive neuropsychological battery. 16 Other studies of patients treated with DMTs have shown some benefit in neuropsychological function as measured by the Paced Auditory Serial Addition Test (PASAT), but comprehensive neuropsychological testing was not performed.…”
Section: Methodsmentioning
confidence: 99%
“…In the CDD, participants must recall, following a 25-minute delay, how symbols and digits have been paired in a "key" that they are shown. 20,23 ICE is a weighted summary score capturing the entire ANAM battery performance. The ICE score is computed by weighting the throughput scores from five ANAM tests (PRO, CDD, Matching-to-Sample, Logical Relations, and Mathematical Processing) so that each score contributes equally to the total ICE score.…”
Section: Changes In Fatigue During Treatment With Natalizumabmentioning
confidence: 99%
“…The FTT was developed as part of the Halstead-Reitan Battery (Halstead, 1947) and consists in a test of fine psychomotor performance, measured through self-directed manual motor speed and control (Christianson & Leathem, 2004;Strauss, Sherman, & Spreen, 2006), recurrently employed to assess impairment resulting from traumas, diseases, and other clinical conditions, such as brain injury (Arnold et al, 2005;Hubel, Yund, Herron, & Woods, 2013a;Kane, Roebuck-Spencer, Short, Kabat, & Wilken, 2007), Alzheimer's disease (Arnold et al, 2005;Dwolatzky et al, 2003Dwolatzky et al, , 2004Kane et al, 2007), Parkinson's disease Shimoyama, Ninchoji, & Uemura, 1990), multiple sclerosis Wilken et al, 2003), mild cognitive impairment (Dwolatzky et al, , 2004, and mental retardation (Arnold et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, its efficacy still justifies its place among the most used instruments (Strauss et al, 2006). Therefore, recently, in an attempt to overcome such limitations, several computerized versions have emerged, which are able to measure the response time more precisely, requiring less time to administer, and generating instant scoring (Wilken et al, 2003). The FTT is now part of several recent batteries, such as the Computerized Neurocognitive Battery (Coleman, Moberg, Ragland, & Gur, 1997;Gur et al, 2010), the Automated Neuropsychological Assessment Metrics-ANAM 4tm Reeves, Winter, Bleiberg, & Kane, 2007;Wilken et al, 2003), the FePsy (Aldenkamp et al, 2002;Stewart et al, 2006), and the Neurotrax TM Mindstreams TM (Dwolatzky et al, , 2004Schweiger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%